Prognostic and Predictive Markers in Cancer. Issue 2 (10th June 2013) - Conley, Barbara A.; Taube, Sheila E.
Abstract : The elucidation of the human genome and advances in knowledge about molecular abnormalities, signaling pathways, influence of the local tissue milieu and the relevance of genetic polymorphisms offer hope of designing more effective, individualized cancer treatment plans. Although the scientific and medical literature is replete with reports of putative prognostic or predictive markers for cancer, few new diagnostics have been incorporated into routine clinical practice. Criteria are needed to a) identify markers that have the promise to be clinically useful; b) assess the best methodology for clinical evaluation of the markers in question and c) confirm or validate that using the marker adds useful information compared to using standard prognostic factors alone. This review presents a methodology for the clinical evaluation of putative prognostic and predictive markers in cancer, with considerations of pitfalls in the early evaluation, rationale for development and optimization of assay methodology, and examples of possible clinical trials for assessing the clinical utility of putative markers.